The relationships between service quality, customer satisfaction and buying intentions in the private hospital industry - C. Boshoff; B. Gray (South African Journal of Business Management, 2004)
The objective of this study was to investigate whether superior service quality and superior transaction-specific customer satisfaction will enhance loyalty (as measured by purchasing intentions) among patients in the private health care industry. The research design allowed an assessment of the relative impact of individual dimensions of service quality and transaction-specific customer satisfaction on two dependent variables, namely loyalty (as measured by intentions to repurchase) and customer satisfaction, the latter measured as `overall' or cumulative satisfaction.The results reveal that the service quality dimensions Empathy of nursing staff and Assurance impact positively on both Loyalty and Cumulative satisfaction.The customer satisfaction dimensions Satisfaction with meals, Satisfaction with the nursing staff and Satisfaction with fees all impact positively on both Loyalty and Cumulative satisfaction.
Keywords: 650